2007
DOI: 10.1111/j.1524-4725.2007.33199.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of High-Viscosity 2-Octyl Cyanoacrylate Tissue Adhesive versus Sutures in Repairing Facial Wounds Following Mohs Micrographic Surgery

Abstract: HVOCA tissue adhesive is cosmetically equivalent to epidermal sutures in the linear repair of facial wounds following MMS. This technique represents an additional option for Mohs surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Higher viscosity is advantageous in reducing the risk of migration of the adhesive away from the wound and thus may improve wound cosmesis. [7] Within 5-10 days, as the wound re-epithelialises, the adhesive generally sloughs off. [7] Premature sloughing of the adhesive might result from topical ointment and frequent cleansing of wounds treated with OCA.…”
Section: Discussionmentioning
confidence: 99%
“…Higher viscosity is advantageous in reducing the risk of migration of the adhesive away from the wound and thus may improve wound cosmesis. [7] Within 5-10 days, as the wound re-epithelialises, the adhesive generally sloughs off. [7] Premature sloughing of the adhesive might result from topical ointment and frequent cleansing of wounds treated with OCA.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue adhesive glues have been used for many years to treat small wounds and cuts. Various recent studies have shown that adhesive glues can be successfully applied to different mucosa and skin, as in the treatment of aphthous ulcers [5], lip closure [6], facial wounds after Mohs surgery [7], and nail bed injuries [8]. Other studies have shown successful use of adhesive glues in obstetrics and gynecology such as skin closure of Pfannenstiel incision at the end of cesarean section and repair of evulsion of clitoris [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…3 Another study investigated the use of a liquid adhesive, high-viscosity 2-octyl cyanoacrylate compared with superficial sutures for repair of Mohs facial defects and found similar cosmetic results. 4 Although our study is the first to compare superficial sutures with adhesive strips for repair of cheek defects, one study compared superficial sutures with adhesive strips and tissue adhesive (octylcyanoacrylate) for skin closure after phlebectomy. There was no difference in cosmetic outcome at 1 year, but faster closure (although not statistically significant) and decreased expense was achieved with adhesive strips.…”
Section: Discussionmentioning
confidence: 99%